Perbandingan Model PjBL dan DL Pada Materi Struktur Atom Terhadap Aktivitas dan Hasil Belajar Siswa Kelas X SMAN 2 Kupang - Lolita Agusta Magdalena Parera; Yosua Ximenes; Heru Christianto (Lembaga Pengembangan Kinerja Dosen, 2025)
An investigation was conducted at A State Senior High School in Kupang City, NTT.to assess how Project-Based Learning (PjBL) and Discovery Learning (DL) models differentially impact student learning activities and outcomes when teaching atomic structure. Adopting a quasi-experimental design with a nonequivalent control group, the study collected data through comprehensive activity questionnaires, observation sheets, and pretest/posttest instruments. The findings clearly showed that PjBL significantly boosted student learning activities, with an average score of 81.19, considerably higher than the 66.15 observed in the DL group. This significant difference was statistically confirmed by an independent samples t-test. Regarding learning outcomes, the PjBL group's average (70.97) was marginally better than the DL group's (68.89), but this difference did not reach statistical significance. It is suggested that limitations in learning time may have played a role in the learning outcomes. This study concludes that PjBL is superior for enhancing student engagement and activity, while both PjBL and DL are equally effective in improving student learning outcomes. Ultimately, the choice of a learning model should be strategically aligned with educational goals, subject matter, and the unique characteristics of the classroom to maximize student achievement.